Cultural Reactions: Reality Pedagogy in Science Education - Heil, Grant (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
The United States and its school systems are becoming increasingly diverse. Science educators are tasked with stimulating the minds of multiple ethnic and cultural groups during their pedagogical career. Some science educators may have the mission of cultivating students in a location where none of the students share the educator’s cultural background. Culturally responsive pedagogy assists educators in bridging the cultural gaps between students and presents science content in a method that is relatable. Reality Pedagogy is a subset of culturally responsive education that can be implemented by educators in diverse settings. Reality Pedagogy consists of five foundational blocks: Cogenerative Dialogues, Coteaching, Cosmopolitanism, Context, and Content. Case studies have validated the effectiveness of Reality Pedagogy in diverse pedagogical science environments.